2014
DOI: 10.1083/jcb.201308136
|View full text |Cite
|
Sign up to set email alerts
|

Talin-bound NPLY motif recruits integrin-signaling adapters to regulate cell spreading and mechanosensing

Abstract: β3 integrin residue Y747 is required for cell spreading and paxillin adapter recruitment to substrate-bound integrins in response to substrate stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 76 publications
14
83
0
Order By: Relevance
“…Consistent with this, β3 tail mutations that resulted in normal integrin activation and talin binding but decreased cell spreading, were recently described (Pinon et al, 2014). A previous study showed that expression of β1-K752L in integrin β1-null fibroblasts did not alter the integrin activation status or the ability of the cells to adhere to fibronectin and laminin-111; however this mutation did inhibit cell spreading and migration (Armulik et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Consistent with this, β3 tail mutations that resulted in normal integrin activation and talin binding but decreased cell spreading, were recently described (Pinon et al, 2014). A previous study showed that expression of β1-K752L in integrin β1-null fibroblasts did not alter the integrin activation status or the ability of the cells to adhere to fibronectin and laminin-111; however this mutation did inhibit cell spreading and migration (Armulik et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…[22][23][24] Talin, a cytoplasmic protein, is known to bind to the cytoplasmic tail of integrin and increase its affinity in response to various agonists acting on platelets. [25,26] Thus, we hypothesized that indothiazinone's antiplatelet activity may be ascribed to its ability to inhibit the function of talin.…”
Section: Effect Of Indothiazinone On Talin-induced Pac1 Bindingmentioning
confidence: 99%
“…Integrin transmembrane proteins and the talin cytoskeletal binding protein play critical roles in cell migration [8]. PI4,5P 2 and PI4,5P 2 synthesizing enzymes control integrin activation by talin in the process termed “inside-out” integrin signaling [74, 75]. Adhesion, spreading and migration are all directly influenced by the activation state of integrins and talin in focal adhesion complexes [74, 75].…”
Section: Pip Kinases Regulate Pi45p2 Effectors In Cell Migrationmentioning
confidence: 99%
“…PI4,5P 2 and PI4,5P 2 synthesizing enzymes control integrin activation by talin in the process termed “inside-out” integrin signaling [74, 75]. Adhesion, spreading and migration are all directly influenced by the activation state of integrins and talin in focal adhesion complexes [74, 75]. PI4,5P 2 generation by a focal adhesion-targeting splice isoform of PIPKIγ, PIPKIγi2, putatively provides a discrete pool of PI4,5P 2 required for talin activation during assembly of focal adhesion complexes [37, 44, 76].…”
Section: Pip Kinases Regulate Pi45p2 Effectors In Cell Migrationmentioning
confidence: 99%